Crystal structure of folic acid dihydrate, C29H29N2O6(H2O)2. Issue 1 (20th October 2014) - Kaduk, James A.; Crowder, Cyrus E.; Zhong, Kai
Abstract : The crystal structure of folic acid dihydrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Folic acid dihydrate crystallizes in space group P 21 21 21 (#19) with a = 7.275 78(3), b = 8.632 17(4), c = 32.417 19(22) Å, V = 2035.985(18) Å 3, and Z = 4. The structure is dominated by a three-dimensional network of hydrogen bonds. The dicarboxylic acid side chain occurs in a bent conformation, helping explain the ability of folate derivatives to coordinate metal cations. The powder pattern has been submitted to ICDD for inclusion in future releases of the Powder Diffraction File™.